Birth weight and cognitive function in young adult life: historical cohort study. - Sørensen, H. T. (1997)
OBJECTIVE: To examine the relation between birth weight and cognitive function in young adult life. DESIGN: Retrospective cohort study based on birth registry data and cognitive function measured during evaluation for military service. SUBJECTS: 4300 Danish conscripts born between 1973 and 1975. MAIN OUTCOME MEASURES: Mean score in the Boerge Prien test of cognitive function; score is the number of correct answers to 78 questions and correlates with full scale intelligence quotient (IQ). RESULTS: Mean score in the Boerge Prien test increased from 39.9 at a birth weight of < or = 2500 g to 44.6 at a birth weight of 4200 g even after adjustment for gestational age and length at birth, maternal age and parity, and other variables. Above a birth weight of 4200 g the test score decreased slightly. CONCLUSION: Birth weight is associated with cognitive performance in young adult life. Interference with fetal growth may influence adult cognitive performance.